Women’s mental health: acute impact of COVID-19 pandemic on domestic violence - Sediri, Sabrine (Arch Womens Ment Health, 2020)
The coronavirus disease 2019 (COVID-19) pandemic created a situation of general distress. Although the focus has been initially more on the physical health during the pandemic, mental health concerns linked to the lockdown have quickly risen. This study aims to assess the effect of the COVID-19-related lockdown on Tunisian women’s mental health and gender-based violence. An online survey was conducted, using the Depression Anxiety and Stress Scales (DASS-21) and the Facebook Bergen Addiction Scale (FBAS). We chose a female-exclusive social group on Facebook and used the snowball sampling method. A total of 751 participants originating from all the Tunisian regions completed the questionnaire. More than half of the participants (57.3%) reported extremely severe distress symptoms, as per the DASS-21. Those who had a history of mental illness and who were allegedly abused during lockdown were found to have more severe symptoms of depression, anxiety, and stress. Around 40% of women reported problematic social media use. Violence against women also reportedly increased significantly during the lockdown (from 4.4 to 14.8%; p < 0.001). Psychological abuse was the most frequent type of violence (96%). Women who had experienced abuse before the lockdown were at an increased risk of violence during lockdown (p < 0.001; OR = 19.34 [8.71–43.00]). To our knowledge, this is the first study that evaluates the acute impact of COVID-19 on mental health and violence against women in Tunisia, Africa, and the Arab world. It may be a sound basis for developing a more effective psychological intervention aimed at women in these regions.